Customer Experience Rating for Achieving Loyalty & Satisfaction - Bujang, Safian; Abdullah, Firdaus; Abd Rashid, Muhammad Hafiz (Information Management and Business Review, 2024)
Business organizations are turning to innovative goods, new markets, and inorganic growth prospects to generate income as global marketplaces change dramatically and player competition heats up. However, providing a superior and distinctive customer experience for financial services represents the biggest chance for long-term revenue development. Creating a Customer Experience Rating (CXR), a measurement of customer experience in the Malaysian banking industry is the primary goal of this project. According to the statistical analysis findings, the CXR had a high degree of reliability and proved construct validity by reaching both convergent and discriminant validity. The Malaysian population enjoys positive bank experiences, as indicated by the customer experience rating 7.37. The results of this study can be used by practitioners, managers, and regulators to better understand customer experiences and create marketing strategies that will enhance the operational environment, increase customer loyalty and satisfaction, and foster positive word-of-mouth.